Soil bacterial communities of three types of plants from ecological restoration areas and plant-growth promotional benefits of Microbacterium invictum (strain X-18) - Liu, Chao; Zhuang, Jiayao; Wang, Jie; Fan, Guohua; Feng, Ming; Zhang, Shutong (Frontiers in Microbiology, 2022)
Microbial-assisted phytoremediation promotes the ecological restoration of high and steep rocky slopes. To determine the structure and function of microbial communities in the soil in response to changes in soil nutrient content, the bacterial communities of rhizospheric soil from three different plants, i.e., Robinia pseudoacacia, Pinus massoniana, and Cynodon dactylon were analyzed using Illumina sequencing technology. High-quality sequences were clustered at the 97% similarity level. The dominant genera were found to be RB41, Gemmatimonas, Sphingomonas, Bradyrhizobium, and Ellin6067. The Tukey HSD test results showed that the abundance of RB41 and Gemmatimonas were significantly different among the three plant types (P < 0.01). The soil chemical properties analyses suggested that significant differences in rhizospheric soil nutrient content among the three plant types. The soil bacterial communities were further studied using the correlation analysis and the Tax4Fun analysis. The outcomes of these analyses suggested that Gemmatimonas could be the indicator genus in response to changes in the soil nutrient content. Besides, the genes involved in metabolism were the major contributor to soil nutrients. This study showed that soil nutrients affect the soil bacterial community structure and function. In addition, pot experiments showed that Microbacterium invictum X-18 isolated from the rhizospheric soil of R. pseudoacacia significantly improved soil nutrient content and increased R. pseudoacacia growth.